Analysis of Environmental Factors with Dengue Hemorrhagic Fever in Guntur, Demak, Indonesia - Hariyanti, Fika; Raharjo, Mursid; Joko, Tri (Journal of Community Medicine and Public Health Research, 2024)
Guntur district is one of the districts that is classified as endemic for dengue fever in Demak, Indonesia. In the last three years, there have been consecutive cases or deaths due to Dengue Hemorrhagic Fever (DHF). Based on the epidemiological triangle concept, the emergence of dengue fever can be caused by an imbalance between host (human) factors, the agent as the cause, and the supporting environment. Environmental factors facilitate contact with agents consisting of the physical, social and biological environment. The physical environment that influences the occurrence of dengue fever cases includes house layout, type of container, frequency of draining the container, availability of lids on containers, altitude and climate. DHF cases in Guntur District in 2022 were 67 cases (IR 0.8 per 1,000 population). The case sample in this study was 86 respondents consisting of 43 case groups and 43 as controls. Sampling was taken in Guntur, Demak, Indonesia. The results showed that the factors having influence on the DHF were landfill materials, landfill volume, landfill availability, frequency of landfill draining, and the presence of larvae. The risk factors for dengue fever are the material of the water reservoir, the frequency of draining the water reservoir, the volume of the landfill, and the presence of larvae. People who used cement/soil landfill materials had a 3.529 greater chance of contracting dengue fever. People with less reliable behavior in draining landfills had a 5.569 times greater chance of contracting dengue fever, and people whose water reservoirs containing larvae had a 17.939 times greater chance of contracting dengue fever.